Electrochemical biosensing in oncology: a review advancements and prospects for cancer diagnosis - Sana Noreen; Izwa Ishaq; Muhammad Hamzah Saleem; Baber Ali; Syed Muhammad Ali; Javed Iqbal (Cancer Biology & Therapy)
Early and precise diagnosis of cancer is pivotal for effective therapeutic intervention. Traditional diagnostic methods, despite their reliability, often face limitations such as invasiveness, high costs, labor-intensive procedures, extended processing times, and reduced sensitivity for early-stage detection. Electrochemical biosensing is a revolutionary method that provides rapid, cost-effective, and highly sensitive detection of cancer biomarkers. This review discusses the use of electrochemical detection in biosensors to provide real-time insights into disease-specific molecular interactions, focusing on target recognition and signal generation mechanisms. Furthermore, the superior efficacy of electrochemical biosensors compared to conventional techniques is explored, particularly in their ability to detect cancer biomarkers with enhanced specificity and sensitivity. Advancements in electrode materials and nanostructured designs, integrating nanotechnology, microfluidics, and artificial intelligence, have the potential to overcome biological interferences and scale for clinical use. Research and innovation in oncology diagnostics hold potential for personalized medicine, despite challenges in commercial viability and real-world application.